Explaining consumer brand-related activities on social media: An investigation of the different roles of self-expression and socializing motivations. (October 2017) - de Vries, Lisette; Peluso, Alessandro M.; Romani, Simona; Leeflang, Peter S.H.; Marcati, Alberto
Abstract: People undertake various brand-related activities on social media that differ in levels of engagement. Companies, however, want to know how to motivate consumers to become involved in the relatively more engaging activities, as such activities are more likely to lead to increased sales. In this article, we focus on activities that are highly engaging (such as writing product reviews) or moderately engaging (such as rating products). Based on self-determination theory, the present research identifies different motivations for engaging in different brand-related activities on social media. We provide evidence indicating that the motivations of self-expression and socializing play primary roles in leading people to participate in highly engaging activities (i.e. creating one's own content online) and in moderately engaging activities (i.e. collaborating with others to contribute to content). These findings have implications for both theory and practice insofar as they specify how to stimulate consumers to perform relatively more engaging brand-related activities on social media. Highlights: An overarching framework explains which motivations affect brand-related activities. The framework is tested by a survey and an experimental study. Specific motivations drive activities that entail different levels of engagement. Expressing oneself motivates people to generate online content. Socializing with others motivates people to contribute content.